Peranan metoda pendidikan pada Sasana Silih Asih dalam rehabilitasi wanita tuna susila - Sri Rahayu Astuti (Universitas Padjadjaran?, 1986)
Educational methods to rehabilitate prostitutes; case study at Sasana Silih Asih, a rehabilitation center in Cirebon, Jawa Barat.